FORECASTING FOR AGRICULTURAL PRODUCTION USING ARIMA MODEL - SenthamaraiKannan.K , K.M.Karuppasamy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Paddy is a most important food crop in India moreover second most in over world. ARIMA is one of the most valuable forecasting techniques in prediction to the future events in time series analysis. This data was collected from Ministry of Agriculture & Farmers Welfare, Government of India. The ARIMA (Box-Jenkins) model was used for paddy production forecast from south India. The concert of fitted ARIMA model used for Andhra Pradesh, Karnataka, Kerala and Tamil Nadu, ARIMA(0,1,1), ARIMA(0,1,1), ARIMA(0,1,2) and ARIMA(0,1,1). Examine through compute the various Parameter estimate measures BIC, RMSE, MAPE, MAE, MaxAPE and MaxAE are used. The main objective of this work is designing and implementation of time series model for crop production with the comparison of each and every state to verify this result.